Utilization of Optical Fibers as Displacement Sensors - Ikmal Maulana; Adiva Nuris Safira; Islakhul Nailil Umami; Anisa Fitri; Feyza Rizqia Ramadhani (Globe: Publikasi Ilmu Teknik, Teknologi Kebumian, Ilmu Perkapalan, 2024)
An experiment examined micrometer shifts in optical fibers to understand sensor characteristics: range, linearity, sensitivity, and resolution. Findings showed voltage output decreases with fiber length. The fiber coupler sensor's range was 2 mm, and the fiber bundle sensor's was 25 mm.While not perfectly linear, the study identified operational ranges using y = ax + n. The fiber bundle had two linear regions: Front Linear (0.2-1.6 mm) with R² = 0.9918 and Rear Linear (2.3-8.3 mm) with R² = 0.977. The fiber coupler's linear trend spanned 0.3-2.1 mm with an R² of 0.944. Sensitivity was 4668.5 V/mm (front) and 780.91 V/mm (rear) for the fiber bundle, and 215.79 V/mm for the fiber coupler. Resolution was 0.0107 µm (front), 0.0640 µm (rear) for the fiber bundle, and 0.2317 µm for the fiber coupler. These findings shed light on optical fiber shift sensor parameters.